2014
DOI: 10.1159/000368881
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Perinatal Care and Outcomes in Newborns at the Limit of Viability in Spain: The EPI-SEN Study

Abstract: Background: Advances in perinatal care can influence morbidity and mortality in newborns at the limit of viability. Knowledge of these changes over time may help improve clinical decision making, optimize resource allocation and increase quality of care. Objectives: To evaluate the influence on morbidity and mortality of changes introduced in the perinatal care of preterm infants (22-26 weeks' gestational age, GA) in Spain between two consecutive periods (2002-2006 and 2007-2011). Methods: An analysis of prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 24 publications
0
27
0
12
Order By: Relevance
“…Survival of extremely preterm infants has improved in recent years; however, both neurodevelopmental and/or sensorial impairment still affect a substantial number of survivors. 22 Term infants resuscitated with 100% oxygen exhibited prolonged oxidative stress after birth and had increased mortality. 4,23 Moreover, epidemiologic studies have shown that exposure to oxygen even for brief periods of time immediately after birth is associated with an increased incidence of childhood cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Survival of extremely preterm infants has improved in recent years; however, both neurodevelopmental and/or sensorial impairment still affect a substantial number of survivors. 22 Term infants resuscitated with 100% oxygen exhibited prolonged oxidative stress after birth and had increased mortality. 4,23 Moreover, epidemiologic studies have shown that exposure to oxygen even for brief periods of time immediately after birth is associated with an increased incidence of childhood cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Fischer's exact test showed that the incidence of ADHD is more frequent in boys (22%) than girls (19%) (P value = 0.038). The test also showed that there was no significant difference between six-and seven-year-old children in terms of ADHD (P value 2 Iran J Psychiatry Behav Sci. 2017; 11(1):e5394.…”
Section: Resultsmentioning
confidence: 95%
“…Following the advances in perinatal care, an increasing number of preterm infants reach childhood (2). Negative effects of preterm birth on neurodevelopmental and psychiatric development of children and adolescents have been well documented (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…García-Muñoz y colaboradores reportaron una incidencia de sepsis tardía de 50,5% en los menores de 26 semanas y estuvo asociada con la prolongada estancia hospitalaria, similar a nuestros resultados (41,05%) para la sepsis tardía (17) .…”
Section: Discussionunclassified